Las tecnologías de la información y la comunicación en los procesos de orientación para el estudio a distancia - Ruiz Carrascosa, Juan (REOP - Revista Española de Orientación y Psicopedagogía, 2014)
RESUMEN El artículo que presentamos ofrece una investigación sobre la utilización de las TIC en el desarrollo de un plan de acogida para nuevos estudiantes de la Universidad Nacional de Educación a Distancia (UNED) y del programa de orientación desarrollado, que ofrecen información y asesoramiento para que los alumnos conozcan la metodología del estudio a distancia, así como los recursos virtuales disponibles para el desarrollo de los procesos de enseñanza y aprendizaje en educación superior. Presentamos los resultados de la evaluación de este programa, en el que han participado 140 estudiantes de 12 carreras diferentes y del curso de acceso para mayores de 25 años. ABSTRACT This article reflects the results of a research about the use of ICT for the development of a welcoming plan for entering students in the public Spanish Open University (UNED). Within this plan, a guidance program has been carried out for students to become familiar with distance learning methodology, as well as the virtual resources available for the development of the teaching-learning processes in higher education. Students have used both the computing facilities at the university and their own PCs at home in order to access the university’s website. Attention has been paid to the competencies necessary for distance learning, the orientations for study planning, self-regulated study techniques and exam preparation. The program evaluation results are provided. 140 students from 12 different degrees and from the access course for students over 25 years took part in the study. Two questionnaires were provided to measure the relevance of the virtual platform, the contents developed and the resources and materials used. Both a descriptive analysis and a correlation analysis among the different variables involved have been conducted. Conclusions and suggestions for the improvement of the guidance program are offered.